(untitled) (London Journal of Research In Humanities and Social Sciences, 2024)
The article is devoted to the analysis of the theory of the labor origin of the language, which is the most important element of Nikolai Marr. The author reveals some of the nuances of its creation and notes the inconsistency of this theory. Based on this, questions are raised about the relevance of N. Marrs theory of glottogenesis and the relevance of the entire theory of the labor origin of the language as a whole for modern science. Important attention is paid to the sources of N. Marrs New doctrine of language. First of all, the author analyzes the Marxist theory of the labor origin of man and his language, which was especially developed in the work of Friedrich Engels The role of labor in the process of the transition from ape to man. The second most important place is occupied by the tool concept of the origin of the language of Ludwig Noir. This concept received an excellent schematic explication in his work The tool of labor and its significance in the history of the development of mankind. Of particular importance is the concept of mimic language by Wilhelm Wundt, presented in his work The Soul of Man and Animals, which is not related to the labor theory of the origin of language. Two versions of the labor principle of glottogenesis that is, theories of F. Engels and L. Noir most influenced the formation of the N. Marrs New doctrine of language, one of the deep developments of which was a detailed, contradictory and extremely complicated concept of the origin of the language. It was based on the hypothesis of the era of manual language and on the hypothesis of the decisive role of tools in the formation of sound language and logical thinking. The main drawback of the conception of Nikolai Marr was its inconsistency due to the fact that the scientist, without any evidence, introduced into his theory the principles of labor-magic activity and the four primary elements of language (SAL, BER, JON, RO). These contradictions and theoretically unsubstantiated constructions did not cancel the originality and constructiveness of a number of ideas embedded in Marrism. However, due to these contradictions and shortcomings, the glottogenetic concept of Nikolai Marr could not develop into a coherent theory. It remained a collection of interesting and important, but often strange, fantastic, grotesque ideas.